Untargeted metabolomics reveals the alteration of metabolites during the stewing process of Lueyang black-bone chicken meat - Wang, Ling; Li, Guojin; Gao, Jie; Cheng, Jia; Yuan, Zhengnan; Lu, Hongzhao; Zeng, Wenxian; Zhang, Tao (Frontiers in Nutrition, 2024)
Black-bone chicken meat is rich in nutritional substances and bioactive compounds.Stewing is a traditional and healthy cooking style for black-bone chicken meat. However, the alteration of metabolites in chicken meat during stewing is still unknown. Here, a comprehensive analysis of metabolites was performed in fresh chicken meat (FM), short-term heat-pretreated meat (PM), fully cooked meat (CM) and chicken soup (CS) via untargeted metabolomics. By comparison, 200, 992 and 891 significantly differentially metabolites (DMs) were identified in the PM vs FM, CM vs FM and CS vs FM comparisons, respectively. These DMs mainly included amino acids, peptides, carbohydrates and lipids. During the heating process, the abundances of Ser, Ala, Tyr, niacinamide, galactose, guanosine 3'monophosphate and inosine 5'-monophosphate in chicken meat significantly decreased and were partially dissolved in the soup. Due to the hydrolysis of phospholipids, the relative contents of unsaturated lipids, especially a range of lysophosphatidylcholines, lysophosphatidylethanolamines, arachidonic acid and derivatives, increased in fully cooked 2 meat. These results indicated that pretreatment had little impact on the changes in metabolites in chicken meat. During stewing, the dissolved amino acids, carbohydrates and nucleic acids could enhance the taste quality of chicken soup, and the high abundance of unsaturated lipids could promote the nutritional quality of black-bone chicken meat.